Accountability for Realists. Issue 1 (3rd April 2018) - Stokes, Susan
ABSTRACT: In Democracy for Realists, Christopher Achen and Larry Bartels argue that voters are shortsighted and punish incumbents for politically irrelevant outcomes. These failings, in the authors' view, mean that voters are incapable of holding politicians to account. But Achen and Bartels overstate voters' failure to engage in effective retrospective voting. The authors also understate the degree to which accountability can be compatible with voters' being myopic, such as when early- and late-term performance are correlated. Achen and Bartels also overlook evidence that the American state acted as an insurer against social risk long before the New Deal, a fact that points to voters using relevant criteria (not irrelevant ones) when they appear to punish incumbents for natural disasters. Finally, while accountability is an important consequentialist reason for democracy, we should keep in mind non-consequentialist justifications for this system of government, in particular its instantiation of political equality.